1997
DOI: 10.1074/jbc.272.51.32163
|View full text |Cite
|
Sign up to set email alerts
|

c-Jun NH2-terminal Kinases Target the Ubiquitination of Their Associated Transcription Factors

Abstract: Regulatory proteins are often ubiquitinated, depending on their phosphorylation status as well as on their association with ancillary proteins that serve as adapters of the ubiquitination machinery. We previously demonstrated that c-Jun is targeted for ubiquitination by its association with inactive c-Jun NH 2 -terminal kinase (JNK). Phosphorylation by activated JNK protects cJun from ubiquitination, thus by prolonging its half-life. In the study reported here, we determined the ability of JNK to target ubiqui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
129
1

Year Published

1999
1999
2007
2007

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 130 publications
(136 citation statements)
references
References 36 publications
(62 reference statements)
6
129
1
Order By: Relevance
“…It has indeed been shown that phosphorylation by JNK protects substrates from JNK-targeted ubiquitinylation and subsequent proteolytic degradation (Fuchs et al, 1996(Fuchs et al, , 1997Musti et al, 1997). Interestingly, we recently identi®ed UBC9, a ubiquitin conjugating enzyme (Kovalenko et al, 1996), as a potential partner of ATFa, using a two-hybrid screen in yeast (unpublished results).…”
Section: Atfa a Jnk Carriermentioning
confidence: 91%
See 1 more Smart Citation
“…It has indeed been shown that phosphorylation by JNK protects substrates from JNK-targeted ubiquitinylation and subsequent proteolytic degradation (Fuchs et al, 1996(Fuchs et al, , 1997Musti et al, 1997). Interestingly, we recently identi®ed UBC9, a ubiquitin conjugating enzyme (Kovalenko et al, 1996), as a potential partner of ATFa, using a two-hybrid screen in yeast (unpublished results).…”
Section: Atfa a Jnk Carriermentioning
confidence: 91%
“…The JNKs were initially identi®ed by their ability to bind the N-terminus of the c-Jun protein, on a site (now de®ned as the docking site) encompassing amino acids 33 ± 47, and to subsequently phosphorylate the Ser63 and Ser73 residues (Whitmarsh and Davis, 1996;Minden and Karin, 1997). Phosphorylation of these sites stimulates the ability of c-Jun to activate transcription of speci®c target genes by a mechanism which remains largely unknown: it has been proposed, for example, that this phosphorylation may indirectly protect c-Jun from ubiquitinylation, thereby prolonging its half-life (Fuchs et al, 1996(Fuchs et al, , 1997; alternatively, this phosphorylation may induce the dephosphorylation of Thr231, Ser243 and Ser249 residues and, as a consequence, increase cJun DNA-binding activity (Papavassiliou et al, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…C/EBPa physically interacts with JNK1 in vitro and in vivo c-Jun N-terminal kinase (JNK) is an important member of mitogen-activated protein kinase (MAPK) family and regulates the activity of its physically associated substrates (Fuchs et al, 1997). Therefore, we chose JNK to study the biological relevance of its interaction with C/EBPa.…”
Section: Proteomic Identification Of the C/ebp-dbd Multiprotein Complmentioning
confidence: 99%
“…In addition to c-Jun, JNKs also phosphorylate other AP-1 proteins, including JunB and JunD [25,95]. The regulatory effect of JNKs on AP-1 transcription might not only be due to phosphorylation of Jun but may also involve JNKregulated ubiquitin-mediated degradation of AP-1 proteins [66,67]. JNKs appear to be essential in cytokine and stressinduced activation of AP-1 but are not required for AP-1 activation in response to other stimuli.…”
Section: Map Kinase Signalingmentioning
confidence: 99%